Perioperative outcomes of frenectomy using laser versus conventional surgery: a systematic review - Lebret Clément; Garot Elsa; Amorim Pereira Mélodie; Fricain Jean-Christophe; Catros Sylvain; Fénelon Mathilde (EDP Sciences, 2021)
Introduction: Frenectomy is an oral surgical procedure usually performed with a scalpel. Several authors recently reported the interest of laser, as a minimally invasive and efficient alternative tool to perform frenectomy. This study aimed to compare the perioperative management of patients requiring a frenectomy using scalpel versus laser. Materials and methods: A systematic review of the literature has been carried out from Pubmed and Scopus databases following PRISMA guidelines. PICO method was used to select the relevant articles. Clinical studies comparing the perioperative outcomes of patients requiring frenectomies using scalpel versus laser were included. Results: Ten articles involving 375 patients were included. Pre-operative parameter (anxiety before surgery) and per-operative data such as anesthesia, surgery duration, bleeding, suture and difficulty were assessed. The post-operative outcomes investigated were pain, analgesics use, functional discomfort, edema, healing and satisfaction of patients. Laser achieved satisfactory peri-operative outcomes such as shorter operative time, without suturing requirement, as well as less post-operative pain and functional discomfort. Discussion: The low number of eligible studies, the different type of lasers used and heterogeneity across the methodology of the selected studies were the limits of the study. Conclusion: Laser-assisted surgery became an attractive tool to perform oral soft tissue surgery.